2017
DOI: 10.47203/ijch.2017.v29i01.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bristle Hardness & Duration of Manual Tooth brushing on Plaque Control

Abstract: Background: Oral health is an integral part of general health. Poor oral health can have adverse effect on general health hence a good oral health is very essential, which in turn is achieved by good oral hygiene. Even though, the concept of good oral hygiene evolved 5000 years back, it is only in the beginning of 19th century it gained more importance. (1) Dental caries and periodontal disease are the most commonly occurring diseases affecting mankind. Dental plaque is a very important factor in the causation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…19 Brushing teeth with hard bristles may remove plaque better than soft bristles do, but more potentially cause soft tissue trauma. 25 In this study, as many as 57.38% of respondents use tools other than toothbrushes to clean their teeth, which are toothpicks. No respondents are using other types of interdental cleaners.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…19 Brushing teeth with hard bristles may remove plaque better than soft bristles do, but more potentially cause soft tissue trauma. 25 In this study, as many as 57.38% of respondents use tools other than toothbrushes to clean their teeth, which are toothpicks. No respondents are using other types of interdental cleaners.…”
Section: Discussionmentioning
confidence: 80%
“…Some respondents 14.75% always brush their teeth after breakfast and 44.26% always brush their teeth before going to bed at night, only 11.48% do at the recommended times (after breakfast and before going to bed at night). Most respondents claim to brush their teeth for 2 minutes or more (60.66%) and brush all surfaces of the teeth The practices of oral health maintenance are categorized as good (32)(33)(34)(35)(36)(37)(38)(39)(40), adequate (22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and bad (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Table 3 shows the practices of oral health maintenance of respondents with 50.82% being adequate, 47.54% good, while a small portion of 1.64% being bad category (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Jeong et al (2018) reported that ultra-soft toothbrushes have a similar efficacy to soft toothbrushes in removing plaque and reducing dental abrasion [8]. However, it has also been reported that while the use of ultra-soft toothbrushes can reduce the plaque index relative to the baseline, the decrease does not attain an optimal level, which may affect recommendations for their use [9,10].…”
Section: Introductionmentioning
confidence: 99%